The effects of bacterial endotoxin LPS on synaptic transmission at the neuromuscular junction - Cooper, Robin L. (Heliyon, 2019)
The direct action of bacterial lipopolysaccharides (LPS) endotoxin was shown to enhance synaptic transmission and hyperpolarize the membrane potential at low doses, but block glutamatergic receptors and decrease observable spontaneous events at a high dosage. The dosage effects are LPS type specific. The hyperpolarization is not due to voltage-gated potassium channels or to activation of nitric oxide synthase (NOS). The effects are induced directly by LPS, independent of an immune response.